Faktor-Faktor Yang Berhubungan Dengan Kualitas Tidur Pasien Di ICCU RSUD Ulin Banjarmasin - Sari, Indah; Hafifah, Ifa; Choiruna, Hasby Pri (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Sleep disturbance in critical patients maybe related with the disease suffered, environmental disturbance,interruption of treatment procedures, anxiety disorder and medication factors. Identification and treatment ofpatient sleep disorders is an important goal for nurses. Nurses must understand the nature of sleep, factors thatinfluence sleep and sleep habits of patients to get the need for sleep and rest. Know the factors related to thequality of sleep of patients in the ICCU Ulin Banjarmasin Hospital. Observational analytic with cross sectionaldesign and using purposive sampling technique with a sample of 33 respondents at ICCU Ulin BanjarmasinHospital. The instrument of this research was in the form of RCSQ questionnaire, STAI, symptoms of physicalillness, environmental disorders, disruption of treatment procedures and medical records. Based on theanalysis using the Fisher Exact test, there is a relationship between sleep quality and symptoms of physicalillness (p value=0,016), there is a relationship between sleep quality and environmental disorders (pvalue=0,004), there is a relationship between sleep quality and disruption of treatment procedures (pvalue=0,014), anxiety disorder (p value=0,002), there is a relationship between sleep quality and medicationfactors (p value=0,006). Sleep quality is a condition in which the sleep experienced by an individual producesfreshness when he wakes up from sleep. Awakening from sleep, especially at night in intensive care patients caninterfere with sleep quality and usually caused by several factors, namely symptoms of physical illness,environmental disturbance, interruption of treatment procedures, anxiety disorder and medication factors.